Parler pour gouverner: Trois études sur le discours présidentiel français - ARNOLD, EDWARD; Labbé, Cyril; Labbé, Dominique; Moniere, Denis (Laboratoire d'Informatique de Grenoble, 2016)
Three statistical studies applied to presidential discourse (vocabulary, themes and style).The campaigns for the presidential elections of 2002, 2007 and 2012 reveal personalisation, tension and a growing level of aggression between candidates. The analysis of televised debates between the two finalists since 1974 leads to the same conclusions, and shows that political conditions of the moment prevail over the left-right divide and over the personalities of the candidates. The mapping of the political communication of seven presidents since 1958 shows that they talk a lot and prefer to use the medium of speeches rather than interviews or press conferences. Trois études de statistique appliquée au discours présidentiel (vocabulaire, thèmes et style). Les campagnes pour les élections présidentielles de 2002, 2007 et 2012 indiquent une personnalisation, une tension et une agressivité croissante entre les candidats. L’analyse des débats télévisés entre les deux finalistes depuis 1974 aboutit aux mêmes conclusions et montre que la conjoncture politique du moment l’emporte sur le clivage droite-gauche et sur la personnalité des candidats. Le recensement de la communication des sept présidents depuis 1958 montre qu’ils parlent beaucoup et qu’ils privilégient l’allocution plutôt que les entretiens ou les conférences de presse.
Keywords: France; Elections; President; Political discourses; Lexicometry; Stylometry; Digital Humanities; Identities in Transformation; Linguistics